Explaining trends in alcohol-related harms in Scotland 1991–2011 (II): policy, social norms, the alcohol market, clinical changes and a synthesis. (March 2016) - McCartney, G.; Bouttell, J.; Craig, N.; Craig, P.; Graham, L.; Lakha, F.; Lewsey, J.; McAdams, R.; MacPherson, M.; Minton, J.; Parkinson, J.; Robinson, M.; et al.
Abstract: Objective: To provide a basis for evaluating post-2007 alcohol policy in Scotland, this paper tests the extent to which pre-2007 policy, the alcohol market, culture or clinical changes might explain differences in the magnitude and trends in alcohol-related mortality outcomes in Scotland compared to England & Wales (E&W). Study design: Rapid literature reviews, descriptive analysis of routine data and narrative synthesis. Methods: We assessed the impact of pre-2007 Scottish policy and policy in the comparison areas in relation to the literature on effective alcohol policy. Rapid literature reviews were conducted to assess cultural changes and the potential role of substitution effects between alcohol and illicit drugs. The availability of alcohol was assessed by examining the trends in the number of alcohol outlets over time. The impact of clinical changes was assessed in consultation with key informants. The impact of all the identified factors were then summarised and synthesised narratively. Results: The companion paper showed that part of the rise and fall in alcohol-related mortality in Scotland, and part of the differing trend to E&W, were predicted by a model linking income trends and alcohol-related mortality. Lagged effects from historical deindustrialisation and socio-economic changes exposures also remain plausible from the available data. This paper shows that policy differences or changes prior to 2007 are unlikely to have been important in explaining the trends. There is some evidence that aspects of alcohol culture in Scotland may be different (more concentrated and home drinking) but it seems unlikely that this has been an important driver of the trends or the differences with E&W other than through interaction with changing incomes and lagged socio-economic effects. Substitution effects with illicit drugs and clinical changes are unlikely to have substantially changed alcohol-related harms: however, the increase in alcohol availability across the UK is likely to partly explain the rise in alcohol-related mortality during the 1990s. Conclusions: Future policy should ensure that alcohol affordability and availability, as well as socio-economic inequality, are reduced, in order to maintain downward trends in alcohol-related mortality in Scotland. Highlights: Policy differences or changes prior to 2007 are unlikely to explain the trends. Some alcohol social norms may be different. Increased alcohol availability is likely to be part of the explanation for the increase. Substitution effects with illicit drugs or clinical changes are unlikely to be important. Changing incomes and alcohol availability are likely to be part of the explanation.